Slices and lumps division and aggregation in law and life - Fennell, Lee Anne (University of Chicago Press, 2019)
How things are divided up or pieced together matters. Half a bridge is of no use at all. Conversely, many things would do more good if they could be divided up differently: Perhaps you would prefer a job that involves a third less work and a third less pay or a car that materializes only when needed and is priced accordingly? Difficulties in "slicing" and "lumping" shape nearly every facet of how we live and work--and a great deal of law and policy as well. Lee Anne Fennell explores how both types of challenges--carving out useful slices and assembling useful lumps--surface in myriad contexts, from hot button issues like conservation and eminent domain to developments in the sharing economy to personal struggles over work, money, time, diet, and exercise. Yet the significance of configuration is often overlooked, leading to missed opportunities for improving our lives. With a technology-fueled entrepreneurial explosion underway that is dividing goods, services, and jobs in novel ways, and as urbanization and environmental threats raise the stakes for assembling resources and cooperation, this is an especially exciting and crucial time to confront questions of slicing and lumping. The future of the city, the workplace, the marketplace, and the environment all turn on matters of configuration, as do the prospects for more effective legal doctrines, for better management of finances and health, and more. This book reveals configuration's power and potential--as a unifying concept and as a focus of public and private innovation.